Transformation of dissolved organic matter by two Indo‐Pacific sponges - Hildebrand, Tabea; Osterholz, Helena; Bunse, Carina; Grotheer, Hendrik; Dittmar, Thorsten; Schupp, Peter J.; Osterholz, Helena; 4 Leibniz‐Institute for Baltic Sea Research Warnemünde Rostock Germany; Bunse, Carina; 3 Institute for Chemistry and Biology of the Marine Environment (ICBM), University of Oldenburg Oldenburg Germany; Grotheer, Hendrik; 1 Alfred‐Wegener‐Institut Helmholtz‐Zentrum für Polar‐ und Meeresforschung Bremerhaven Germany; Dittmar, Thorsten; 2 Helmholtz‐Institute for Functional Marine Biodiversity at the University of Oldenburg (HIFMB) Oldenburg Germany; Schupp, Peter J.; 2 Helmholtz‐Institute for Functional Marine Biodiversity at the University of Oldenburg (HIFMB) Oldenburg Germany (Limnology and Oceanography, 2022)
Dissolved organic matter (DOM) is the largest organic carbon reservoir in the ocean and an integral component of biogeochemical cycles. The role of free‐living microbes in DOM transformation has been studied thoroughly, whereas little attention has been directed towards the influence of benthic organisms. Sponges are efficient filter feeders and common inhabitants of many benthic communities circumglobally. Here, we investigated how two tropical coral reef sponges shape marine DOM. We compared bacterial abundance, inorganic and organic nutrients in off reef, sponge inhalant, and sponge exhalant water of Melophlus sarasinorum and Rhabdastrella globostellata. DOM and bacterial cells were taken up, and dissolved inorganic nitrogen was released by the two Indo‐Pacific sponges. Both sponge species utilized a common set of 142 of a total of 3040 compounds detected in DOM on a molecular formula level via ultrahigh‐resolution mass spectrometry. In addition, species‐specific uptake was observed, likely due to differences in their associated microbial communities. Overall, the sponges removed presumably semi‐labile and semi‐refractory compounds from the water column, thereby competing with pelagic bacteria. Within minutes, sponge holobionts altered the molecular composition of surface water DOM (inhalant) into a composition similar to deep‐sea DOM (exhalent). The apparent radiocarbon age of DOM increased consistently from off reef and inhalant to exhalant by about 900 14C years for M. sarasinorum. In the pelagic, similar transformations require decades to centuries. Our results stress the dependence of DOM lability definition on the respective environment and illustrate that sponges are hotspots of DOM transformation in the ocean. Helmholtz Institute for Functional Marine Biodiversity at the University of Oldenburg Ministry for Science and Culture of Lower Saxony http://dx.doi.org/10.13039/501100010570 Carl‐von‐Ossietzky University Oldenburg Alfred‐Wegener‐Institute, Helmholtz‐Center for Polar and Marine Research ...